Chiang Kai-shek’s “secret deal” at Xian and the start of the Sino-Japanese War - Tsang, Steve (Palgrave Macmillan, 2015)
Using newly available archives, particularly the diary and the presidential papers of Chiang Kai-shek, this article challenges the conventional interpretations of the Xian Incident (1936), in particular the widely held belief that the kidnapping of China’s leader Chiang by two rebellious generals forced him to form a united front with the Communist Party to confront Japanese aggression, and of the outbreak of the Sino-Japanese War 7 months later. It puts forth the interpretation that full-scale war between China and Japan was started not by Japan but by Chiang after a Japanese provocation, and the united front was only formed after Chiang ordered his best army units to attack Japanese forces in Shanghai in August 1937 turning it into the largest land battle after the First World War. It must be noted, however, that Japan acted provocatively and aggressively in a local incident outside Beijing a month earlier. Chiang decided on war not because he reached an agreement with the Chinese Communists to form a united front whilst a captive in Xian but because in Xian he received a signal from Josef Stalin that the Soviet Union would support him in a war with Japan. Chiang read Stalin right and the Soviet Union became the largest supplier of weapons to China in the first 4 years of China’s 8-year war with Japan. The hitherto unknown or “secret deal” Chiang made in Xian was an implicit one with Stalin, not with the Chinese Communist Party or its man on the spot Zhou Enlai.